2016
DOI: 10.2807/1560-7917.es.2016.21.13.30181
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cerebral malformations and dysfunction in fetuses and newborns following the 2013 to 2014 Zika virus epidemic in French Polynesia

Abstract: We detected an unusual increase in congenital cerebral malformations and dysfunction in fetuses and newborns in French Polynesia, following an epidemic of Zika virus (ZIKV), from October 2013 to March 2014. A retrospective review identified 19 cases, including eight with major brain lesions and severe microcephaly, six with severe cerebral lesions without microcephaly and five with brainstem dysfunction without visible malformations. Imaging revealed profound neurological lesions (septal and callosal disruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
171
0
13

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(199 citation statements)
references
References 13 publications
(23 reference statements)
11
171
0
13
Order By: Relevance
“…Case reports indicate that fetuses and infants of pregnant women with asymptomatic Zika virus infection might be at risk for microcephaly and other severe brain defects (9,10). Following pregnant women with laboratory evidence of possible Zika virus infection in the surveillance system, regardless of symptoms, allows better characterization of the full impact and consequences of infection to the mother and her offspring, and might allow for better stratification of risk for adverse congenital outcomes (1).…”
Section: Discussionmentioning
confidence: 99%
“…Case reports indicate that fetuses and infants of pregnant women with asymptomatic Zika virus infection might be at risk for microcephaly and other severe brain defects (9,10). Following pregnant women with laboratory evidence of possible Zika virus infection in the surveillance system, regardless of symptoms, allows better characterization of the full impact and consequences of infection to the mother and her offspring, and might allow for better stratification of risk for adverse congenital outcomes (1).…”
Section: Discussionmentioning
confidence: 99%
“…Hydranencephaly, intracranial calcifications, destructive lesions of the posterior fossa, hydrothorax, ascites, subcutaneous edema, and arthrogryposis have been described in severe cases (68) (69) . It is important to rule out other infectious agents that are known to induce microcephaly (38) (70) before ascribing it to Zika virus infection.…”
Section: Zika Virus and Microcephalymentioning
confidence: 99%
“…The spectrum of disease caused by Zika virus among adults and children is still being investigated and defined, but it is clear in the most recent epidemic in South and Central America, Mexico, and the Caribbean islands that when infection occurs in pregnant women, fetuses appear to be at increased risk for a poor clinical outcome. [2][3][4][5][6][7][8][9] The most significant effect of the Zika virus on the fetus is the occurrence of neuronal necrosis and microcephaly-this has been demonstrated in neuroimaging studies performed both before delivery and following the birth of infected infants. 2,3,7 Pathology studies have been shown to be an important component of the public health investigation of emerging infections, contributing to the understanding of the mechanisms of tissue injury, for example, human immunodeficiency virus, Ebola virus, hantavirus, West Nile virus, and many others.…”
mentioning
confidence: 99%